EDUKASI KESELAMATAN DAN KESEHATAN KERJA PETUGAS GIZI DI RSI KABUPATEN KARAWANG - Widhiantika, Wieke; Darmawan, Wendi; Yuliana, Chaerani Tri; Jumaedi, Jumaedi; Muhidin, Muhidin (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2023)
The occupational health and safety (OHS) education program for nutrition workers at RSI Kabupaten Karawang aims to enhance their understanding and skills in preventing various work-related risks they frequently encounter. Key risks, such as ergonomic issues, improper use of personal protective equipment (PPE), injuries from kitchen equipment, and exposure to hazardous chemicals, are the main focus of this program. Through an educational approach that includes awareness campaigns, practical training, and simulations, there was a significant reduction in risk levels after the program was implemented. Prior to the intervention, ergonomic risks reached 40%, improper PPE use was 30%, kitchen equipment injuries accounted for 25%, and chemical exposure was 20%. After the education program, all risk categories showed a decrease, with ergonomic risks reduced to 20%, PPE misuse to 15%, equipment injuries to 12%, and chemical exposure down to 10%. These results demonstrate that OHS education can effectively improve work safety and the well-being of nutrition workers, as well as support the creation of a safer and healthier hospital work environment. This program could serve as a model for sustainable OHS implementation in other healthcare institutions